Estudiantes en tornos tradicionales y a distancia. Perfiles motivacionales y percepciones del contexto - Danilo Donolo; Analía Chiecher; María Cristina Rinaudo (Universidad de Murcia, 2004)
In this article the intention is to describe and to compare motivational characteristic and perceptions of the context of learning on the part of students who learn in traditional and virtual contexts. Participated in the study 89 adult student who attended a course. The course included an traditional instance and a virtual one. The analyzed data were gathered by means of the administration of two instruments: (1) section Á of the Motivated Strategies Learning Questionnaire (Pintrich et al., 1991) that evaluates students motivational aspects and (2) a questionnaire of Zoller (1992) that evaluates perceptions of the context. In order to compare motivational profiles and perceptions of the context of the students in traditional and virtual contexts, the total group was divided in two sub-groups; this way, 42 students gave answer to the administered instruments being centered in the traditional instance of the course, whereas rest 47 did it taking care of the virtual instance. The statistical analysis through t test with independent samples informs significant differences in three scales: extrinsic orientation, control beliefs and anxiety. Respect to the perceptions of the context the results did not inform significant differences between the considered groups; that is to say, the students -in traditional or virtual contexts- declared to have had similar experiences.